2000
DOI: 10.1054/bjoc.2000.1146
|View full text |Cite
|
Sign up to set email alerts
|

True

Abstract: The 52-kDa activator protein (AP)-2 is a DNA-binding transcription factor which has been reported to have growth inhibitory effects in cancer cell lines and in human tumours. In this study the expression of AP-2α was analysed in 303 epithelial ovarian carcinomas by immunohistochemistry (IHC) with a polyclonal AP-2α antibody and its mRNA status was determined by in situ hybridization (ISH) and reverse transcriptase-polymerase chain reaction (RT-PCR). The immunohistochemical expression of AP-2α was correlated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…The transcription factors screened for in vivo association with the epcam promoter were selected based on evidence for a biological role in epcam regulation (Gires et al , 2001; Tai et al , 2007; Yamashita et al , 2007; Sankpal et al , 2009) and their potential role in ovarian cancer (Anttila et al , 2000; Reimer et al , 2007; Min and Wei-hong, 2009; Oettgen, 2010). …”
Section: Resultsmentioning
confidence: 99%
“…The transcription factors screened for in vivo association with the epcam promoter were selected based on evidence for a biological role in epcam regulation (Gires et al , 2001; Tai et al , 2007; Yamashita et al , 2007; Sankpal et al , 2009) and their potential role in ovarian cancer (Anttila et al , 2000; Reimer et al , 2007; Min and Wei-hong, 2009; Oettgen, 2010). …”
Section: Resultsmentioning
confidence: 99%
“…However, in the current study, we observed exclusively a cytoplasmic expression pattern of AHRR proteins in gastric adenocarcinoma tissues. As was reported by previous researches, some other transcription factors have been described to be both cytoplasmic and nuclear expression in many kinds of human malignancies [25][27]. For the reason of these differences, Wang W et al supposed that immunohistochemistry may only evaluate the end products of gene expression [27].…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have reported that other transcription factors exhibit both cytoplasmic and nuclear expression in many human malignancies [31], [44]. To explain this difference in localization, Wang et al suggested that immunohistochemistry might only evaluate the end products of gene expression [31].…”
Section: Discussionmentioning
confidence: 99%